Dangerous, subversive, seditious: the reversal of the path of violence - Costa, Luiz Cláudio da (2022)
In this essay, I address the installation Dangerous, subversive, seditious (Notebooks of the Brazilian people) by Leila Danziger, made for the exhibition “Hiatus: the memory of dictatorial violence in Latin America”. The starting point of the exhibition curated by Márcio Seligmann-Silva were the archives of the National Truth Commission (CNV). The objective of this essay is to think about the representation of violence and the victims of the dictatorship as it appears in the work of the artist from Rio de Janeiro. For this, I dialogue with three authors: Emmanuel Lévinas, Judith Butler and Susan Sontag. Highlighting the signs of an elaboration in process where flaws and fissures provoke the viewer’s gaze and provide the presence of unique apparitions and stories, Danziger builds an atlas that misinterprets the portrayal of victims and reverses the path of violence.